Barriers to Incorporating Artificial Intelligence in Chemistry Instruction in Post-Primary Education in Orlu Education Zone II, Imo State - Metu, Sharon Ifechi; Okore, Glory Jerry; Nwaodu, Mary-claret; Nwosu, Chinonye Cynthia (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
This study aimed to determine the impediment to the incorporation of Artificial Intelligence in Chemistry Instruction in Post-primary education in Orlu Education Zone II, Imo State. A descriptive survey research design was adopted in conducting this research. The population of the study comprises of Chemistry teachers from all the 41-government owned post primary schools in Orlu Education Zone II. A census sampling technique was employed which constitutes 41 chemistry teachers comprising 16 males and 25 females. Data were gathered using a four-point Likert questionnaire instrument with a reliability coefficient of 0.71 ascertained using test-retest methodology. The t-test, mean, and standard deviation statistical tools were used to assess the generated data at the 0.05 level of significance. Two research questions and one hypothesis guided the study. The findings indicated a lack of technical assistance, training and resources, low computer self-efficacy, opposition to innovation, and lack of AI knowledge which obstructed the incorporation of Artificial Intelligence in chemistry instruction in post-primary education. In light of the results, attending workshops and seminars was advised for chemistry teachers in order to foster a positive knowledge about AI, increase their computer self-efficacy, and demonstrate an interest in innovation towards AI in chemistry instruction in post-primary education in Imo state.